Intra-aneurysmal pressure changes during stent-assisted coiling. - Piotr Piasecki (PLoS ONE, 2020)
We aimed to examine aneurysm hemodynamics with intra-saccular pressure measurement, and compare the effects of coiling, stenting and stent-assisted coiling in proximal segments of intracranial circulation. A cohort of 45 patients underwent elective endovascular coil embolization (with or without stent) for intracranial aneurysm at our department. Arterial pressure transducer was used for all measurements. It was attached to proximal end of the microcatheter. Measurements were taken in the parent artery before and after embolization, at the aneurysm dome before embolization, after stent implantation, and after embolization. Stent-assisted coiling was performed with 4 different stents: LVIS and LVIS Jr (Microvention, Tustin, CA, USA), Leo (Balt, Montmorency, France), Barrel VRD (Medtronic/ Covidien, Irvine, CA, USA). Presence of the stent showed significant reverse correlation with intra-aneurysmal pressure-both systolic and diastolic-after its implantation (r = -0.70 and r = -0.75, respectively), which was further supported by correlations with stent cell size-r = 0.72 and r = 0.71, respectively (P<0.05). Stent implantation resulted in significant decrease in diastolic intra-aneurysmal pressure (p = 0.046). Systolic or mean intra-aneurysmal pressure did not differ significantly. Embolization did not significantly change the intra-aneurysmal pressure in matched pairs, regardless of the use of stent (p>0.05). In conclusion, low-profile braided stents show a potential to divert blood flow, there was significant decrease in diastolic pressure after stent placement. Flow-diverting properties were related to stent porosity. Coiling does not significantly change the intra-aneurysmal pressure, regardless of packing density.